Comparison of Anti-Bacterial Activities of Dried Houttuynia Cordara Thunb (Yu Xing Cao) Ethanolic Extracts Against Selected Bacteria - Chia, Woon Ling (2015)
The study was conducted to compare the anti-bacterial activities of 50% and 95% ethanol extract of dried Houttuynia cordata Thunb. (Yu Xing Cao) against selected bacteria. The objectives were to determine the anti-bacterial effect of Houttuynia cordata against three different bacteria which are Staphylococcus aureus, Bacillus subtilis, and Escherichia coli. Two different concentration of ethanol were used in the experiment, which are 50% ethanol and 95% ethanol. In the first procedure, powder form dried Houttuynia cordata and ethonal 50% at a ratio of 1:5 were used, the powder was suspended in 95% ethanol for 7 day. Disc diffusion test is to determine the anti-microbial activities for the two plant extracts. Ethanol 50% and 95% were used as the negative control while Gentamicin was used as positive control groups. Data were collected by measuring the zone of inhibition with ruler or Vernier calliper. There were no zone of inhibition shown by the 50% and 95% ethanol extract of H. cordata, indicating that the extraction do not contain anti-bacterial effect.